Definition and quantification of innovation in interaction. Issue 3 (1st October 2016) - Filippi, Stefano; Barattin, Daniela
Abstract : A method for determining which product is more innovative than others and for determining the degree of innovation could be useful. Furthermore, such determination could focus on human–machine interaction. Based on a set of trends of evolution in interaction and on existing methods for the definition and quantification of innovation and related concepts, this research defines and quantifies innovation in interaction. This approach can help designers select the most innovative solution concepts and can help marketing experts establish their selling strategies; in addition, final users can be aided when choosing the best product to buy. This paper describes the definition of new metrics that focus on interaction in conjunction with a computational pipeline that uses these metrics to assess the presence and degree of innovation in interaction. An early validation of the results in the field is reported as well.